Influence of rotational isomerism on two-photon absorption properties of FTC chromophores - 韩广超 赵珂 刘朋伟 张立立 (Chinese physics B, 2012)
The influence of rotational isomerism on the two-photon absorption （TPA） of FTC chromophores has been investi- gated using the quadratic response theory with the B3LYP functional. Eight rotamers induced by three rotatable single bonds in the molecule are fully optimized, and it is found that their conformational energies are nearly degenerate. Our calculations demonstrate that rotational isomerism has an important effect on the TPA cross sections. For a certain rotamer, the maximum TPA cross section is enhanced significantly. In addition, in the longer wavelength region, the rotational isomerism could lead to a large shift of the TPA position.